Varicella-zoster virus: identification of genotypes in cases of varicella and herpes zoster in the Municipalities of Ananindeua, Belém and Marituba, Pará State, Brazil - Costa, Marcos Rogério Menezes da (2019)
This is a cross-sectional study in which the clinical criteria for inclusion of the samples was the clinical suspicion and/or onset of symptoms of chickenpox or shingles in order to genotype varicella-zoster virus (VZV) by the polymerase chain reaction (PCR) and sequencing techniques, with a search of single nucleotide polymorphisms (SNP) subsequently. From November 2008 to March 2012, 93 samples (85 cases of varicella and eight herpes zoster) were collected from oral, nasal swab and secretion of ruptured vesicles in several anatomical sites (49 male and 44 female). Dumas and Oka parental strains were included as European genotypes of the reference standard (class 1 or 3) and Japanese (class 2) genotypes, respectively. Strains with the SNP variability were classified into a group of genotype describe as Mosaic (class 5). Classes 1 or 3 were identified in 11 samples of VZV, nine cases of varicella and two cases of herpes zoster, while two samples showed the class genotype 5, both cases of varicella. The genotype class 1 or 3 was found in the Municipalities of Ananindeua, Belém and Marituba, Pará State, Brazil, and genotype class 5 only in Ananindeua. PCR was sensitive in just 13 samples of direct vesicles material, but in saliva samples there were not positive results.